Effects of undernourishment on children’s school performance in Peru - León Mendoza, Juan (2019)
The article aims to determine the influence of undernourishment in school performance of all 25 Peruvian regions. For this purpose, with statistical information provided by the Ministry of Education and using the econometric technique of the Grouped Ordinary Least Squares, the regional performances of children in Reading Comprehension and Mathematical with malnutrition and a set of control variables were regressed. The results indicate that at a regional level, there is a statistically significant measure that given a 1% decrease in regional children’s undernourishment rate, there is an increase in performance in Reading Comprehension and Mathematics in 0.52% and 0.27% respectively. The nutritional aspect influences school performance through its effect on the cognitive ability of the child.